2004
DOI: 10.1099/vir.0.19525-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flanking sequences on presentation efficiency of a CD8+ cytotoxic T-cell epitope delivered by parvovirus-like particles

Abstract: We have previously developed an antigen-delivery system based on hybrid recombinant porcine parvovirus-like particles (PPV-VLPs) formed by the self-assembly of the VP2 protein of PPV carrying a foreign epitope at its N terminus. In this study, different constructs were made containing a CD8 + T-cell epitope of chicken ovalbumin (OVA) to analyse the influence of the sequence inserted into VP2 on the correct processing of VLPs by antigen-presenting cells. We analysed the presentation of the OVA epitope inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Flanking sequences have been shown to impact epitope processing but the sequences flanking epitopes did not differ between the two VLPs [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Flanking sequences have been shown to impact epitope processing but the sequences flanking epitopes did not differ between the two VLPs [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In most cases, unmodified nonvectorized peptide Ags fail to elicit virus-specific T cells, unless they are attached to a carrier protein or delivered with a strong adjuvant [8486]. Often, the delivery of peptides in this manner is unsafe and/or promotes Th 2 responses [87, 88], which would not be expected to provide optimal protection against HSV infection [89].…”
Section: The New Vaccines: Multivalent “Asymptomatic” Lipopeptide mentioning
confidence: 99%
“…It has been previously demonstrated that chimeric PPV-VLPs carrying heterologous epitopes, when injected intraperitoneally (i.p) into mice, activate strong CD4+ and CD8+ T-cell responses specific for the foreign epitopes, and these responses are mediated by dendritic (DC) cells and influenced by the flanking sequences [12], [13], [14]. PPV-VLPs are formed by the assembly of 60 copies of the major virus capsid protein (VP2) of PPV [15].…”
Section: Introductionmentioning
confidence: 99%